Maqasid Al-shariah In Ijarah (leasing) Contract Of Islamic Banking System - Adeyemo Wale Lateef; Alawiye Abdulmumin Abdurrazzaq; Syahirah Abdul Shukor; Amalina Ahmad Tajudin (IIUM Press, 2024)
Non-Indexed Publication